US food security and climate change: Agricultural futures - Eugene S. Takle; David Gustafson; Roger Beachy; Gerald C. Nelson; Daniel Mason-D'Croz; Amanda Palazzo (Kiel Institute for the World Economy (IfW), 2013)
Agreement is developing among agricultural scientists on the emerging inability of agriculture to meet growing global food demands. The lack of additional arable land and availability of freshwater have long been constraints on agriculture. However, the increased frequency of extreme and unpredictable weather events, in a manner consistent with the changes predicted by global climate models, is expected to exacerbate the global food challenge as we move toward the middle of the 21st century. These climate- and constraint-driven crop production challenges are interconnected within a complex global economy, where diverse factors add to price volatility and food scarcity. The present report projects the impact of climate change on food security through the year 2050. The analysis presented here suggests that climate change in the first half of the 21st century does not represent a near-term threat to food security in the US due to the availability of adaptation strategies. However, as climate continues to trend away from 20th century norms current adaptation measures will not be sufficient to enable agriculture to meet growing food demand. High-end projections on carbon emissions will exacerbate the food shortfall, although uncertainty in climate model projections (particularly precipitation) is a limitation to impact studies.
Keywords: Q54; Q17; 330; climate change; food security; crop production; United States